Seborrheic dermatitis: predisposing factors and ITS2 secondary structure for Malassezia phylogenic analysis (2013)
Seborrheic dermatitis (SD) is a chronic, widespread skin condition, which is considered a multifactorial disease influenced, in part, by Malassezia spp. opportunistic activities, as well as various endogenous and exogenous factors. Malassezia species are lipophilic, lipid-dependent yeasts that are members of the normal mycobiota of the human skin. Their isolation from SD lesions varies around the world and the study of the relationship among factors such as gender, age, immunosuppressive condition of the patient and SD development, can lead to a better understanding of this disease. To elucidate the association of age and gender with the development of SD and to precisely determine the Malassezia species involved in the disease, samples were obtained from 134 individuals, including individuals without lesions, human immunodeficiency virus positive patients, individuals with seborrheic dermatitis, and HIV patients with seborrheic dermatitis. Malassezia spp. were identified by phenotypic and genotypic methods and a phylogenetic analysis was performed using Bayesian inference. This study revealed that age and gender are not predisposing factors for SD development, and that the most frequent species of Malassezia related to SD development among the Colombian population is M. restricta. We also report the isolation of M. yamatoensis for the first time in Colombia, and propose an ITS2 secondary structure from Malassezia taxa that can be used for precise identification and to establish more robust phylogenetic relationships.